Intrinsic foot muscle size and associations with strength, pain and foot-related disability in people with midfoot osteoarthritis. (January 2023) - Gong, Qun; Halstead, Jill; Keenan, Anne-Maree; Milanese, Steve; Redmond, Anthony C.; Arnold, John B.
Abstract: Background: To compare intrinsic foot muscle size between people with and without symptomatic midfoot osteoarthritis, and examine the association between muscle size and strength, pain and foot-related disability. Methods: Twenty-three participants with symptomatic midfoot osteoarthritis and 23 age, sex and BMI matched controls were included. Intrinsic foot muscle cross-sectional area was measured using MRI. Hand-held dynamometry was used to assess foot and ankle muscle strength, and foot-related pain and disability was measured using Manchester Foot Pain & Disability Index. Findings: Small and non-statistically significant differences were found in intrinsic foot muscle cross-sectional area between the two groups (effect sizes 0.15–0.26, p  > 0.05). Muscle strength was reduced in the midfoot osteoarthritis group, with differences of 12–33% (effect sizes 0.47–1.2). In the control group, moderate positive associations) existed between foot muscle cross-sectional area and lesser digits flexor strength ( r  = 0.5 to 0.7, p  < 0.05). Conversely, in the midfoot osteoarthritis group, negligible positive associations were found ( r  < 0.3, p  > 0.05). Associations between foot muscle cross-sectional with and pain and disability scores in the midfoot osteoarthritis group were negligible ( r  < −0.3, p  > 0.05). Interpretation: Despite reductions in maximal isometric muscle strength, midfoot osteoarthritis does not appear to be associated with reduced intrinsic foot muscle cross-sectional area measured by MRI. Muscle compositional or neural factors may explain the reductions in muscle strength and variation in symptoms in people with midfoot osteoarthritis and should be investigated. Highlights: We compared intrinsic foot muscle size in midfoot osteoarthritis and controls. Midfoot osteoarthritis was not associated with reduced intrinsic foot muscle size. Muscle size was not associated with strength, foot pain or disability.